Analisis Kinerja Aparatur Desa dalam Pelayanan pada Masyarakat Desa di Desa Silumajang Kecamatan No. IX-X Kabupaten Labuhanbatu Utara - Pebru Arjuna; Abdul Kadir; Nina Angelia (Jurnal Ilmiah Administrasi Publik dan Pemerintahan (JIAPP), 2023)
The study aims to determine the ferformance of the Village Apparatus in service to the Silumajang Village comudity District NA. IX-X Labuhanbatu Utara. Regency and what are the obstacles and constraintseksprienced by the Village Apparatus in providing services to the Silumajang Village community. The method in this research is a qualitative method, with data collection techniques through interviews, observation and documentation. Data infinity by triangulating sources, techniques and time. The analysis was carried out with an interactive model of data reduction, data presentation and conclusion drawing. The results of this study indicate that the ferformance of the Village Apparatus in Silumajang Village is well measured in the six indicators according to Van Metter and Van Horn in the service policy model, namely for indicators can be said to be good covering standards and objectives, the characteristic of the implementing organization, attitudes and communitation. There are still two indicators that are not optimal, namely resources and the social, economic and political environment. As for the inhibiting factors and the obstacles include people who do not realize the importance of the Family Card especially those in neighborhoods far from the Village office, there are still Village Officials who are not yet professionals in carrying out the tasks assigned to them and there is no certainty when the Family Card will be completed.